(untitled) (Bangabandhu Sheikh Mujib Medical College Journal, 2023)
Medical students have a greater risk of depression than students of other subjects. When ragging is added to an already stressful condition, it severely affects their academic and occupational life. Our objective of the study was to explore the student’s perspective on ragging at a government medical college in Bangladesh. This cross-sectional study was carried out in 2022 at Bangabandhu Sheikh Mujib Medical College, Faridpur, Bangladesh. A questionnaire regarding the students’ views and experiences of ragging was distributed among the first-to-fifth-year medical students. To encourage honest responses, the complete anonymity of respondents was maintained. Out of 820 students, 748 (91%) participated in the study. Nearly 1 in every 2 students reported being victims of ragging, with a statistically significant gender difference. More than 65% of victims said that they became afraid of the seniors and distanced themselves from them. Indicators of clinical depression were prevalent among the victims. Total 42% of the victims had to seek help from friends or family members, 92% of the students agreed that ragging affects the mental health of juniors, and it should be a punishable crime. The majority (77%) of the students believed that seniors seek revenge by ragging their juniors. Establishing a sense of superiority and gaining influence over political and cultural groups were also influential reasons for ragging. Awareness against ragging, alternative programs for senior-junior respectful interaction, and strict management for the rule breakers should be ensured to discontinue the culture of ragging and to maintain a healthy academic environment. Bangabandhu Sheikh Mujib Med. Coll. J. 2023;2(1): 14-21